Intellectual property in ACP agriculture: about this dossier - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
This dossier contains over 225 annotated links to information on intellectual property (IP) in ACP agriculture. It is intended for ACP policy makers and researchers who are confronted with the complexities of the various international treaties and agreeme